Generative AI as a Teaching and Learning Tool in Elementary Education: A Systematic Literature Review and Meta-Analysis - Risdiana Nuraini; Emilius German (Institut of Shanti Bhuana, 2025)
Generative artificial intelligence (AI) is a new technology that can make teaching and learning easier in all levels including in elementary schools. It has the potential to improve lessons, make learning more personal, and help students achieve better results. Although many people are interested in using generative AI in education, there is still little clear evidence about how well it works in elementary schools. This study reviews and analyzes research from 2020 to 2025 to understand how generative AI is used, what benefits it offers, what challenges it brings, and how it affects learning compared to traditional teaching methods. This study employed a systematic literature review (SLR) and meta-analysis, following the PRISMA process to thoroughly search for relevant studies. After looking for many studies, 17 studies met the inclusion criteria, and 8 of these were experimental studies analyzed in detail. The results show that generative AI can increase student interest, provide learning suited to individual needs, and support skill growth while reducing some teacher tasks. However, there are still problems such as unequal access to technology, mistakes in AI-generated content, and privacy concerns. It is expected that future researchers will look into bringing generative AI into classrooms carefully, making sure there’s proper infrastructure, teacher training, and clear rules to keep things fair and successful for every student.